Beta HPV Type 15 Can Interfere With NF-κB Activity and Apoptosis in Human Keratinocytes - Paolini, Francesca; Zaccarini, Marco; Francesconi, Arianna; Mariani, Luciano; Muscardin, Luca; Donati, Pietro; Venuti, Aldo (Frontiers in Cellular and Infection Microbiology, 2020)
E7 protein from cutaneous as well as mucosal HPV types can alter NF-κB activity. Conflicting literature data show a HPV-induced up- or down-regulation of the NF-κB pathway in different cell lines. In a previous study we detected the expression of E7 gene of HPV15 in a subungual tumor of a patient affected by incontinentia pigmenti (IP). IP is a rare X-linked genodermatosis in which the IKKγ gene is altered. From observations in transgenic IKKγ defective mice, it was suggested that IKK-deficient cells may undergo rapid hyper-proliferation and apoptosis/necrosis, leading to increased pro-inflammatory cytokine production in the neighboring IKK-positive cells. The objective of this study was to ascertain if beta HPV 15 can alter apoptosis and NF-κB pathway in normal and IKKγ-deficient keratinocytes. The human immortalized keratinocyte cell line (HaCaT), and human primary keratinocyte (HPK) cells were transduced with a retrovirus expressing E6–E7 proteins of HPV 15 and IKKγ was successful silenced mimicking the HPV15 infection and IP. HPV15 E6–E7 gene expression improved NF-κB activity in human keratinocytes even when IKKγ was silenced by siRNA. In IKKγ silenced keratinocyte cells, TNF-α-induced apoptosis was strongly reduced by the expression of HPV15 E6–E7 genes. Beta HPV15 exerted this anti-apoptotic activity by decreasing pro-apoptotic BAK and cleaved Caspase 3 proteins. In conclusion, we can speculate that presence of persistent infection by beta papillomavirus might influence the biological fate of IP by altering NF-κB activation and apoptosis in IKKγ mutated cells, favoring their survival and possibly the development of tumors in the late stage of disease. Taken together, our data reinforce the importance of host genetic background in the pathogenesis of HPV-associated skin lesions.